2008
DOI: 10.1007/s00253-007-1324-y
|View full text |Cite
|
Sign up to set email alerts
|

Purification and biochemical characterization of a broad substrate specificity thermostable alkaline protease from Aspergillus nidulans

Abstract: Aspergillus nidulans PW1 produces an extracellular carboxylesterase activity that acts on several lipid esters when cultured in liquid media containing olive oil as a carbon source. The enzyme was purified by gel filtration and ion exchange chromatography. It has an apparent MW and pI of 37 kDa and 4.5, respectively. The enzyme efficiently hydrolyzed all assayed glycerides, but showed preference toward short- and medium-length chain fatty acid esters. Maximum activity was obtained at pH 8.5 at 40 degrees C. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…Olive oil was substituted by the indicated compound at indicated concentration bands showed CEH activity (37,29, and 22 kDa). These results correspond to those previously reported [14], where it was also stated that the 37-kDa protein corresponds to the alkaline protease PrtA. In the present study, the use of mass spectrometry allowed the identification of the other two bands, which correspond to new cutinases: ANCUT2 and its post-translational processing product, as described in detail below.…”
Section: Effects Of Triacylglycerides and Fatty Acids On Ceh Activitysupporting
confidence: 93%
See 2 more Smart Citations
“…Olive oil was substituted by the indicated compound at indicated concentration bands showed CEH activity (37,29, and 22 kDa). These results correspond to those previously reported [14], where it was also stated that the 37-kDa protein corresponds to the alkaline protease PrtA. In the present study, the use of mass spectrometry allowed the identification of the other two bands, which correspond to new cutinases: ANCUT2 and its post-translational processing product, as described in detail below.…”
Section: Effects Of Triacylglycerides and Fatty Acids On Ceh Activitysupporting
confidence: 93%
“…CEHM was prepared as a minimal nitrate medium with the following modifications: 1.5% starch was added as a carbon source instead of glucose, 0.5% yeast extract was used as an organic nitrogen source, and 0.5% olive oil was added as an inducer [14].…”
Section: Carboxylic Ester Hydrolase Medium (Cehm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Author(s) agree that this article remains permanently open access under the terms of the Creative Commons Attribution License 4.0 International License through thermal stability (Kotlova et al, 2007 , Fe +2, on the contrary, found to inhibit pretense activity (Pena-Montes et al, 2008). and molybdenum and the source of the enzyme detect the important ions heeded.…”
Section: +2mentioning
confidence: 92%
“…is one of the best commercial enzymes products that exist in the market. Each alkaline protease enzyme produced must have a high catalytic ability (Pena-Montes et al, 2008) [4]. So that the analysis of the degree of purity and characterization of enzymes becomes necessary to support the ability of the catalysis enzyme, so it can be maximum applied.…”
Section: Introductionmentioning
confidence: 99%